Short-term exposure to desert dust and sandstorms and all-cause and cause-specific mortality and morbidity: A systematic review and meta-analysis - Aurelio Tobías; Xavier Querol; Marta Roqué; Kaung Suu Lwin; Lei Yuan; Sophearen Ith; Htay Zin Wai; Paul Lester Chua; Iván Solá; Matteo Renzi; Massimo Stafoggia; Masahiro Hashizume (Environment International)
Background: Desert dust and sandstorms raise concerns about their adverse effects on human health. Over the last decade, special attention has been given to mineral dust particles from desert sand. However, evidence from previous literature reviews has yielded inconclusive results regarding their health effects. We aim to systematically synthesize evidence on the short-term health effects of desert dust exposure from major dust source areas. Methods: The bibliographic search was conducted using the MEDLINE (PubMed), Scopus, and Web of Science databases to investigate the health effects of short-term exposure to desert dust in human populations, using time series or case-crossover study designs. Study selection and reporting followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We evaluated the risk of bias (RoB) for individual studies and the certainty of evidence (CoE) for environmental exposures, as developed by a group of experts convened by the World Health Organization (WHO). Publication bias was examined using funnel plots and Begg’s asymmetry test. Results: A total of 71 studies were included in the review, covering data from 1993 to 2024. Most studies focused on Asian and African desert dust, with fewer studies from Arabian, American, and Australian regions. We found a significant increase in the risk for all-cause mortality (Relative Risk, RR = 1.0121, 95 %CI = [1.0045, 1.0199]). In addition, the mortality risk associated with particulate matter less than 10 μm (PM10) was slightly higher on dust days compared to non-dust days, while for particulate matter less than 2.5 μm (PM2.5), the risk was higher on non-dust days. We also observed a significant increase in the risk for cardiovascular mortality (RR = 1.0252, 95 % CI = [1.0100, 1.0407]) during dust days compared to non-dust days, but not for respiratory mortality (RR = 1.0001, 95 % CI = [0.9773, 1.0277]). The risk also increased for cardiovascular (RR = 1.0094, 95 % CI = [1.0014, 1.0174]) and respiratory morbidity (RR = 1.0693, 95 % CI = [1.0188, 1.1224]). Conclusion: Exposure to desert dust and sandstorms is linked to increased risks of all-cause and cardiovascular mortality, as well as respiratory morbidity. The overall evidence quality for each exposure-outcome combination was assessed as moderate, although data limitations prevent the establishment of specific air quality thresholds for desert dust particles. This review highlights the need for targeted public health interventions in affected regions.